ВОЗМЕЩЕНИЕ ЭКОЛОГИЧЕСКОГО ВРЕДА КАК МЕРА ОБЕСПЕЧЕНИЯ ОХРАНЫ ПРИРОДНЫХ ОБЪЕКТОВ ОТ ЗАГРЯЗНЕНИЯ (Journal of actual problems of jurisprudence, 2019)
In the scientific paper studied the current legislation in the field of environmental pollution and the possibility of compensationfor harm caused by pollution. The author studied the ways and methods of economic evaluation of environmental harm.